Bài 1: Tìm x, y, z thõa mãn các điều kiện sau:\(\frac{5z-6y}{4}=\frac{6x-4z}{5}=\frac{4y-5z}{6}\) và\(3x-2y+5z=96\)Bài 2: Tìm x, y, z thão mãn:a. \(2x=3y=7z\) và \(x+y+z-13=0\)b. \(\left(x+y\right):\left(5-z\right):\left(y+z\right):\left(7+y\right)=3:1:2:5\)c. \(\frac{x}{y+z-2}=\frac{y}{x+z+1}=\frac{z}{x+y+1}=x+y+z\)d. \(\frac{x-2003}{2}=\frac{y-2004}{6}=\frac{z-2009}{8}\) và \(x+2y-z=4009\)e. \(\frac{x^2}{9}=\frac{y^2}{25}\) và \(x\cdot...
Đọc tiếp
Bài 1: Tìm x, y, z thõa mãn các điều kiện sau:
\(\frac{5z-6y}{4}=\frac{6x-4z}{5}=\frac{4y-5z}{6}\) và\(3x-2y+5z=96\)
Bài 2: Tìm x, y, z thão mãn:
a. \(2x=3y=7z\) và \(x+y+z-13=0\)
b. \(\left(x+y\right):\left(5-z\right):\left(y+z\right):\left(7+y\right)=3:1:2:5\)
c. \(\frac{x}{y+z-2}=\frac{y}{x+z+1}=\frac{z}{x+y+1}=x+y+z\)
d. \(\frac{x-2003}{2}=\frac{y-2004}{6}=\frac{z-2009}{8}\) và \(x+2y-z=4009\)
e. \(\frac{x^2}{9}=\frac{y^2}{25}\) và \(x\cdot y=15\)
f. \(\frac{x^2-y^2}{3}=\frac{y^2+x^2}{-5}=x^{10}\cdot y^{10}=1024\)
g. \(\frac{x^3}{8}=\frac{y^3}{64}=\frac{z^3}{216}\) và \(x^2+y^2+z^2=14\)
h. \(\frac{2x+1}{5}=\frac{3y-2}{7}=\frac{2x+3y-1}{6x}\)
i. \(\frac{x}{2}=\frac{y}{3}=\frac{z}{5}\) và \(x\cdot y+y\cdot z+x\cdot z=31\)
k. \(7x=3y:5y=7z\) và \(x\cdot y+x\cdot z-y\cdot z=4\)
Bìa 3: Tính
\(Cho
\frac{x}{2}=\frac{y}{3}=\frac{z}{5}\)
Tính
\(a.
A=\frac{5x+3y}{5y-4z}\)
\(b.
B=\frac{x+2y-3z}{3y+2z-5x}\)
\(c.
C=\frac{2y-3z}{x+y+z}\)
Bài 4:
\(Cho
\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\) với \(a+b+c\ne0\) và \(a=2011\)
Tính b và 3b-4c
Có: \(\frac{x}{2}=\frac{y}{5}=\frac{z}{7}\Rightarrow\frac{x}{2}=\frac{y}{5}=\frac{z}{7}=\frac{2y}{10}\)
AD TC DTSBN, có:
\(\frac{x}{2}=\frac{y}{5}=\frac{z}{7}=\frac{2y}{10}=\frac{x-y+z}{2-5+7}=\frac{x+2y-z}{2+10-7}=\frac{x-y+z}{4}=\frac{x+2y-z}{5}\)
\(\Rightarrow\)\(\frac{x-y+z}{4}=\frac{x+2y-z}{5}\Rightarrow\frac{4}{5}=\frac{x-y+z}{x+2y-z}\)
VẬy...
Bài 11:
+ Ta có: \(\frac{x}{2}=\frac{y}{5}=\frac{z}{7}\left(x,y,z\ne0\right).\)
Đặt \(\frac{x}{2}=\frac{y}{5}=\frac{z}{7}=k.\)
\(\Rightarrow\left\{{}\begin{matrix}x=2k\\y=5k\\z=7k\end{matrix}\right.\)
+ Lại có: \(P=\frac{x-y+z}{x+2y-z}.\)
Thay \(x=2k;y=5k\) và \(z=7k\) vào P ta được:
\(P=\frac{2k-5k+7k}{2k+2.5k-7k}\)
\(\Rightarrow P=\frac{2k-5k+7k}{2k+10k-7k}\)
\(\Rightarrow P=\frac{\left(2-5+7\right).k}{\left(2+10-7\right).k}\)
\(\Rightarrow P=\frac{4k}{5k}\)
\(\Rightarrow P=\frac{4}{5}.\)
Vậy \(P=\frac{4}{5}.\)
Chúc bạn học tốt!